Glutamate residue 90 in the predicted transmembrane domain 2 is crucial for cation flux through channelrhodopsin 2 - Ruffert, Karelia; Himmel, Bettina; Lall, Deepti; Bamann, Christian; Bamberg, Ernst; Betz, Heinrich; Eulenburg, Volker (Biochemical and Biophysical Research Communications, 2011)
Channelrhodopsin 2 (ChR2) is a microbial-type rhodopsin with a putative heptahelical structure that binds all-trans-retinal. Blue light illumination of ChR2 activates an intrinsic leak channel conductive for cations. Sequence comparison of ChR2 with the related ChR1 protein revealed a cluster of charged amino acids within the predicted transmembrane domain 2 (TM2), which includes glutamates E90, E97 and E101. Charge inversion substitutions of these residues significantly altered ChR2 function as revealed by two-electrode voltage-clamp recordings of light-induced currents from Xenopus laevis oocytes expressing the respective mutant proteins. Specifically, replacement of E90 by lysine or alanine resulted in differential effects on H(+)- and Na(+)-mediated currents. Our results are consistent with this glutamate side chain within the proposed TM2 contributing to ion flux through and the cation selectivity of ChR2.
EVALuna2:4667